"Soft power" as an instrument for external political influence of the South Korea - Dotsenko, A.; Karlyuk, S. V. (Харківський національний університет ім. В. Н. Каразіна, 2019)
An alternative approach to exercising political influence through "soft power" by South Korea is viewed. Instruments used by Korean diplomacy in its pursuit of its goals are described.
Keywords: foreign policy; national interests; positive image